2000
DOI: 10.1165/ajrcmb.22.6.3925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TNF- α on Expression of ICAM-1 in Human Airway Epithelial CellsIn Vitro

Abstract: Signaling pathways associated with tumor necrosis factor (TNF)-alpha-induced intercellular adhesion molecule 1 (ICAM-1) surface and gene expression were investigated in well differentiated normal human bronchial epithelial (NHBE) cells in air-liquid interface primary culture. Cells were exposed to human recombinant TNF-alpha (hrTNF-alpha; 0.015 to 150 ng/ml [specific activity, 2.86 x 10(7) U/mg]). TNF-alpha enhanced ICAM-1 surface expression (measured by flow cytometry) and steady-state messenger RNA (mRNA) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 38 publications
8
99
0
Order By: Relevance
“…p65 and p50 then enter the nucleus and induce their target genes. The NF-kB-binding site within the ICAM-1 promoter is activated through binding of p65 in THP-1 cells, as well as in various other cell types (e.g., A549 and HUVECs) (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…p65 and p50 then enter the nucleus and induce their target genes. The NF-kB-binding site within the ICAM-1 promoter is activated through binding of p65 in THP-1 cells, as well as in various other cell types (e.g., A549 and HUVECs) (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have demonstrated airway epithelial cell TNF-a responses to be at least partially sensitive to PKC inhibitors. In human bronchial epithelial cells, cigarette smoke-induced, as well as C5a-mediated, IL-8 expression [42] and TNF-ainduced intercellular adhesion molecule-1 expression [43] were blocked by calphostin C, and TNF-a-induced GM-CSF expression was inhibited by the pan-PKC blocker staurosporine [44]. In addition, HEWSON et al [45] reported that PMA-induced expression of the airway mucins MUC5B and MUC5AC by …”
Section: Discussionmentioning
confidence: 99%
“…The NHBE cells utilized in the present study were cultured at the air/liquid interface, resulting in fully differentiated primary cell cultures that maintained a well documented structure and function similar to the in vivo one (8,(21)(22)(23). This air/liquid methodology to culture airway epithelial cells was developed several years ago to provide an ideal in vitro model system to study mechanisms involved in various cellular processes in airway epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…NHBE Cell Culture-Expansion, cryopreservation, and culture of NHBE cells in the air/liquid interface were performed as described previously (8). Briefly, NHBE cells (Clonetics, San Diego, CA) were seeded in vented T75 tissue culture flasks (500 cells/cm 2 ) and cultured until cells reached 75-80% confluence.…”
Section: Methodsmentioning
confidence: 99%